2016
DOI: 10.1007/s00264-016-3121-7
|View full text |Cite
|
Sign up to set email alerts
|

Revision total hip arthroplasty in the United States: national trends and in-hospital outcomes

Abstract: The revision burden has undergone a steady decrease over the ten years studied and the reason for this is likely multifactorial. The South region had a significantly higher revision burden when compared to the rest of the United States. Larger hospitals tend to perform relatively more revisions. Revision THA patients are associated with longer hospital stay, higher complications rate, and higher in-hospital mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 31 publications
2
45
0
1
Order By: Relevance
“…We found that 40% of all HRAs performed in the United States were in the South region. In a recent study, Schwartz et al 33 noted that the number of THA revisions was significantly greater in the South region (32.4%); thus, it seems intuitive that this is the region with the highest number of salvage procedures after failed revision THAs as well. Both the Northeast and Midwest regions had a significant decrease in the overall number of HRAs performed annually, which is in concert with the overall decreased number of HRAs performed nationally.…”
Section: Discussionmentioning
confidence: 98%
“…We found that 40% of all HRAs performed in the United States were in the South region. In a recent study, Schwartz et al 33 noted that the number of THA revisions was significantly greater in the South region (32.4%); thus, it seems intuitive that this is the region with the highest number of salvage procedures after failed revision THAs as well. Both the Northeast and Midwest regions had a significant decrease in the overall number of HRAs performed annually, which is in concert with the overall decreased number of HRAs performed nationally.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, isolated acetabular component revision was not a risk factor for blood transfusion in the 2005 to 2010 group, possibly owing to the fact that a greater number of acetabular revisions in that time frame were performed for osteolysis. 13,73,74 These complex pelvic reconstructions may place patients at increased risk of significant blood loss requiring transfusion, and due to their increased prevalence in earlier years, the protective effect of isolated acetabular component revision on transfusion requirements was not observed in the 2005 to 2010 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In addition, rTHA has previously been associated with lower quality of life, decreased functional outcomes, and an increased complication rate compared with primary THA. 12,13 Mechanical complications are among the most common reasons for performing rTHA, accounting for up to 42 to 50% of all rTHA indications. 14 Aseptic loosening, instability, implant wear, and osteolysis are all potential etiologies for mechanical failure in THA.…”
mentioning
confidence: 99%
“…Increasing numbers of total hip arthroplasties (THA) are performed each year globally [1,2]. This procedure is noted to be highly successful.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure is noted to be highly successful. However, around 7-17% of THAs across the world between 2001 and 2016 required surgical revision for various reasons [1][2][3]. Dislocation of the hip joint is one of the most common reasons for operative revision within the first year [3,4].…”
Section: Introductionmentioning
confidence: 99%